2000
DOI: 10.1051/lait:2000134
|View full text |Cite
|
Sign up to set email alerts
|

Rennet coagulation of skim milk and curd drainage: effect of pH, casein concentration, ionic strength and heat treatment

Abstract: -The effect of the pH of skim milk (6.4 to 6.0), the casein concentration (27 to 36 g . kg -1 ), a reduction in the ionic strength to 0.6 compared to that of unmodified milk and the effect of heat treatment on rennet coagulation, gel syneresis and drainage were tested. Coagulation was measured using a formagraph and by viscoelasticimetry, while syneresis was studied using a centrifugation test. Drainage was followed under conditions similar to those of cheesemaking, using either a mesophilic or thermophilic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
49
2
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 21 publications
(37 reference statements)
11
49
2
3
Order By: Relevance
“…The methodology used involved centrifugation tests and collection of whey versus time by a manual method [7].…”
Section: Curd Preparation and Drainagementioning
confidence: 99%
See 1 more Smart Citation
“…The methodology used involved centrifugation tests and collection of whey versus time by a manual method [7].…”
Section: Curd Preparation and Drainagementioning
confidence: 99%
“…W was the total weight of whey expelled at time (t), W1 and W2 the whey amounts obtained at the end of steps 1 and 2, and τ1 and τ2 the kinetics times of the steps 1 and 2 of whey drainage. This equation was already used in a previous work [7]. A two step exponential equation was chosen to describe W, as it gave a better adjustment to experimental data than a single step equation.…”
Section: Fitting Of Experimental Kinetics Curves To a Modelmentioning
confidence: 99%
“…In addition Hanuš et al (2011) observed that herd, year, and season showed a signifi cant eff ect on milk composition and its technological parameters (including RCT) of milk produced by dairy cows of the Czech Fleckvieh breed. Daviau et al (2000) mentioned that shorter RCT was associated with a decrease in the content of protein, which usually associated also with a decrease in the content of casein. A signifi cant eff ect of season and herd on rennet coagulation time and other parameters of milk technological quality in Holstein cows was observed also by Chládek et al (2011).…”
mentioning
confidence: 99%
“…As proteínas do leite compreendem duas frações: as caseínas, que se apresentam principalmente no estado de partículas coloidais, (micelas) e as proteínas do soro, que estão em solução (DAVIAN et al, 2000;GAUCHERON;LE GRAËT;BRIARD, 2000). O leite bovino tem um conteúdo de proteína, expresso como %N × 6,38, de 30-35 g.L -1 .…”
Section: Introductionunclassified